Studi Metaanalisis Pengaruh Orientasi Kewirausahaan terhadap Kinerja UMKM - Isabela Khoirul Nur Laily; Aniek Hindrayani; Leny Noviani (Departement of Mathematics Education, 2023)
The purposes of this study were to determine the positive effect of entrepreneurial orientation on the performance of SMEs. This research is a quantitative research with a correlation metaanalysis approach with random effect method. The population of this study was related journals that have been published nationally and internationally. The sample in this study were 23 related studies. The sampling technique used was purposive sampling. The results showed that entrepreneurial orientation has a positive and significant effect on the performance of SMEs with a summary effect value of 0,542 and p < 0,001.